Nghiên cứu tổng hợp lignosunfonat từ lignin thu hồi của nhà máy sản xuất bột giấy theo phương pháp kiềm - Hoàng, Phan Huy; Hòa, Doãn Thái (Vietnam Journal of Chemistry, 2014)
In the black liquor of Pulp and Paper Mills, that produces pulp by soda method, contain a large amount of organic compound, especially high content of lignin. Lignin has a lot of important applications in Industry. Lignosulfonate, which is a important deriver of lignin, has many advantages as a surfactant in many fields, for example, in pharmaceutics and pesticide Technology; Petroleum Industry; Printing Industry; Construction; Agriculture… In Vietnam, every year some Pulp and Paper Mills eliminate a large amount of black liquor but they haven’t lignin recovery line. This causes the pollution of environment seriously. Therefore, these black liquor are the available resources to produce lignosulfonate. Finding out the process to separate lignin from black liquor and processing it become trade products such as lignosulfonate not only brings the effect economy but also reduces the influence of polluted black liquor on environment.